Anatomy of a glacial meltwater discharge event in an Antarctic cove. (28th June 2018) - Meredith, Michael P.; Falk, Ulrike; Bers, Anna Valeria; Mackensen, Andreas; Schloss, Irene R.; Ruiz Barlett, Eduardo; Jerosch, Kerstin; Silva Busso, Adrián; Abele, Doris
Abstract : Glacial meltwater discharge from Antarctica is a key influence on the marine environment, impacting ocean circulation, sea level and productivity of the pelagic and benthic ecosystems. The responses elicited depend strongly on the characteristics of the meltwater releases, including timing, spatial structure and geochemical composition. Here we use isotopic tracers to reveal the time-varying pattern of meltwater during a discharge event from the Fourcade Glacier into Potter Cove, northern Antarctic Peninsula. The discharge is strongly dependent on local air temperature, and accumulates into an extremely thin, buoyant layer at the surface. This layer showed evidence of elevated turbidity, and responded rapidly to changes in atmospherically driven circulation to generate a strongly pulsed outflow from the cove to the broader ocean. These characteristics contrast with those further south along the Peninsula, where strong glacial frontal ablation is driven oceanographically by intrusions of warm deep waters from offshore. The Fourcade Glacier switched very recently to being land-terminating; if retreat rates elsewhere along the Peninsula remain high and glacier termini progress strongly landward, the structure and impact of the freshwater discharges are likely to increasingly resemble the patterns elucidated here. This article is part of the theme issue 'The marine system of the West Antarctic Peninsula: status and strategy for progress in a region of rapid change'.